Beyond scarcity marketing: what really drives young consumers to buy from a viral local culinary brand? - Kristia, Kristia; Fridayani, Januari Ayu (Indonesia Research and Study Center, 2025)
The viral culinary trend, marked by limited food availability yet a delectable taste appeal, has become a distinctive phenomenon in Indonesia, prompting long queues of enthusiastic consumers. This study explores various factors influencing young consumers' purchase intention in viral culinary products, focusing on perceived scarcity, electronic word of mouth, and fear of missing out on products from one of viral local culinary vendor. The purposive sampling method was applied, with the criteria of young customers aged 18-26 residing in Yogyakarta or Semarang who have seen reviews about The Golden Geisha restaurant's product reviews on various social media. The study analyzed 600 valid responses with Partial Least Squares Path Modelling with SMART-PLS 4 software. Perceived scarcity alone cannot directly influence young consumers' purchase intention but needs to be mediated by perceived food value. EWOM and FOMO are the other essential factors to be considered to increase the purchase intention of young customers. This study highlights the need for the viral food culinary brand to maintain product quality to differentiate themselves from competitors, maintaining brand reputation on digital social environments and also considers the FOMO factor that can shape consumer behavior of young customers.